Internationalising sea power: ideas of world order and the maintenance of peace, 1890-1919 - Halewood, LM (2019)
Between 1890 and 1919, loosely-grouped communities of policymakers, strategic thinkers, and naval elites in Britain, France, and the United States of America developed visions of a new world order, in which peace would be enforced by sea power. Their designs culminated in the creation of the League of Nations at the end of the First World War. Existing studies of the League project have focused on legal-internationalism, the outbreak of the war, and the role of President Woodrow Wilson. This thesis uses an array of sources from archives in Europe and North America, along with contemporary publications, to present a new interpretation. It argues that debates over imperial defence and grand strategy prior to and during the war, especially in Britain, shaped the design of the League. These conceptions centred on multinational naval co-operation, ‘internationalising’ sea power through the League. Its leading members, Britain, France, and the United States, would wage economic warfare at sea to punish recalcitrant states and uphold the new liberal international order.